Biodiversity of the Scombridae fish in the Syrian marine waters (Latakia University Journal -Biological Sciences Series, 2024)
This research was conducted during November 2021 to September 2023 to determine qualitative composition of the Scombridae fish species had caught from Syrian marine waters (Ras Albasit). Fish samples were collected using the local fishing methods (purse seine, gill nets, trammel nets, long-line and hand lines) The Results showed that 11 species of scombrid namely,  Auxis thazard, Auxis rochei, Euthynnus alletteratus, Katsuwonus pelamis, Sarda sarda, Thynnus thynnus, Thynnus alalunga, Scomberomorus commerson, Scomber japonicas, Scomber colias and Scomber indicus were recorded. Two out of them, Auxis thazard and Scomber indicus are migratory species and this study is first record of them from Syrian marine waters.  Otolith and liver features of all collected species are presented in this study